THE USE OF ROLE PLAY THROUGH IGTV TO IMPROVE STUDENTS’ SPEAKING SKILL OF HARAPAN UTAMA SENIOR HIGH SCHOOL AT BATAM - Pratiwi, Theodesia Lady (Universitas Wiralodra, 2022)
Speaking is one of the most troublesome expertise to ace. It likewise happens to most of the students in Harapan Utama senior high school in Batam. They have numerous problems communicating in English since they believe that English is not a daily language in Indonesia. Therefore, this study aims to find out whether Role-play through the IGTV significantly improves students' ability in speaking skills. This study chose 37 students of grade 10 at Harapan Utama senior high school. This survey research tested the hypotheses that have been set. Therefore, this study used the speaking score (Pre-Test & Post-Test) as the research instrument. From the data conducted by one group pretest and posttest design, the data analysis of t-test shows that the value of Sig. (2-tailed) is 0.00 <0.05. Therefore, there is an average difference between Pre-Test and Post-Test learning outcomes. In addition, based on the Interview, some improvements were achieved in the post-test scores, such as pronunciation, vocabulary, and understanding. Thus, to conclude, using roleplaying through IGTV as a classroom teaching technique can improve students’ speaking skills. Last, this research can be useful and used as an additional guide, particularly in improving the ability of students to speak English.